Borylation of fluorinated arenes using the boron-centred nucleophile B(CN)32− – a unique entry to aryltricyanoborates. Issue 9 (7th July 2017) - Landmann, Johannes; Hennig, Philipp T.; Ignat'ev, Nikolai V.; Finze, Maik
Abstract : SN Ar reactions of the tricyanoboryl dianion B(CN)3 2− with selected fluoroarenes and perfluoropyridine resulted in a wealth of new tricyanoarylborate anions in high yields with high chemo- and regioselectivity. Abstract : The potassium salt of the boron-centred nucleophile B(CN)3 2− (1 ) readily reacts with perfluorinated arenes, such as hexafluorobenzene, decafluorobiphenyl, octafluoronaphthalene and pentafluoropyridine, which results in KF and the K + salts of the respective borate anions with one {B(CN)3 } unit bonded to the (hetero)arene. An excess of K2 1 leads to the successive reaction of two or, in the case of perfluoropyridine, even three C–F moieties and the formation of di- and trianions, respectively. Moreover, all of the 11 partially fluorinated benzene derivatives, C6 F6− n H n ( n = 1–5), generally react with K2 1 to give new tricyano(phenyl)borate anions with high chemo- and regioselectivity. A decreasing number of fluorine substituents on benzene results in a decrease in the reaction rate. In the cases of partially fluorinated benzenes, the addition of LiCl is advantageous or even necessary to facilitate the reaction. Also, pentafluorobenzenes R–C6 F5 (R = –CN, –OMe, –Me, or –CF3 ) react via C–F/C–B exchange that mostly occurs in the para position and to a lesser extent in the meta or ortho positions. Most of the reactions proceed via an SN Ar mechanism. The reaction of 1, 4-F2 C6 H4 with K2 1 shows that an aryne mechanism has to be considered in some cases as well. In summary, a wealth of new stable tricyano(aryl)borates have been synthesised and fully characterized using multi-NMR spectroscopy and most of them were characterised using single-crystal X-ray diffraction.